Створення високопродуктивних сортів малопоширених видів харчових та декоративних рослин, адаптованих до умов південного сходу України - Glukhov, O.Z.; Gorlacheva, Z.S.; Mitina, L.V.; Kustova, O.K.; Zakotenko, S.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
As result of long-term introduction experiment on the base of collection fund of rare food and other useful plant of the Donetsk Botanical Gardens productive, adapted to the steppe conditions released varieties of Morus alba, Lonicera caerulea, Malus × gloriosa, Ocimum basilicum, and Allium ramosum are obtained. They have to be widely applied in culture.